(untitled) (KULT_online, 2015)
Does cognitive capitalism suffer from pathologies that demand attention and cure? Or does it induce pathological reactions in the psyche of its subjects? Whose pathologies are we talking about (individual subjects’, those of the socius or of the economic system itself?) and against what standards of "health" or normality are they measured? The fact that such fundamental questions are not explicitly addressed in the present collection points to what remains one of the core problems of this otherwise most relevant and engaging project: the need for additional, rigorous conceptual work that would elucidate the meaning and function of its core concepts, such as pathology and cure, norm and deviance, and therefore attend to their ontological or biological foundation as grounds for political action.